2019
DOI: 10.1101/700047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biochemical reconstitution of branching microtubule nucleation

Abstract: 16Microtubules are nucleated from specific locations at precise times in the cell cycle. However, the 17 factors that constitute these microtubule nucleation pathways still need to be identified along with 18 their mode of action. Here, using purified Xenopus laevis proteins we biochemically reconstitute 19 branching microtubule nucleation, a nucleation pathway where microtubules originate from pre-20 existing microtubules, which is essential for spindle assembly and chromosome segregation. We 21 found that be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…7, graph). Indeed, recent reconstitution experiments have shown that sites of condensation may serve as branch points for new MTs 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7, graph). Indeed, recent reconstitution experiments have shown that sites of condensation may serve as branch points for new MTs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…See also Supplementary Fig. 5e first be deposited on MTs for augmin to be recruited 21,22 . Furthermore, TPX2 interacts with the tetrameric kinesin Eg5 30,43 , which was recently demonstrated to promote MT nucleation in vitro 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to interphase, mitotic microtubules are shorter and more dynamic; they are nucleated from γ-tubulin complexes either at centrosomes or along pre-existing MTs [1]. Away from centrosomes, MT nucleation requires Ran-dependent liberation of spindle assembly factors such as TPX2, HURP, or NuSAP, together with augmin complexes that are assembled along preexisting microtubules [1,2,3,4,5]. At kinetochores, microtubules interact with several microtubule-associated proteins (MAPs, including microtubule-dependent motors), and appear as cold-resistant MT bundles called kinetochore-fibers (k-fibers) [6].…”
Section: The Biological Contextmentioning
confidence: 99%
“…The ringshaped g-tubulin complex (g-TuRC) serves as the structural template for the initial tubulin assembly, thereby accelerating the initial lag phase (Zheng et al, 1995). However, the g-2 TuRC alone is not an efficient MT nucleator, and efficient nucleation requires association with other proteins, such as CDK5RAP2, XMAP215/ch-TOG, TPX2, and augmin (Alfaro-Aco et al, 2020;Choi et al, 2010;Consolati et al, 2020;Flor-Parra et al, 2018;Tariq et al, 2020;Thawani et al, 2018). Some of these activators likely alter the conformation of g-TuRC to better fit the ends of MT protofilaments (Consolati et al, 2020;Liu et al, 2020;Wieczorek et al, 2020), whereas others cooperate with g-TuRC (Consolati et al, 2020;Flor-Parra et al, 2018;King et al, 2020;Thawani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%